Is Emotion the Engine? Positive Affect as the Mediator Between Employee Mindset and Performance in a Three-Wave Study - Lopez-Bohle, S; Muñoz-Medina, L (Routledge, 2025)
Research in the educational and organizational fields theoretically suggests that individuals’ implicit beliefs are deeply connected with their performance. This study provides insight into the emotional mechanism that connects employees’ mindsets regarding growth (growth vs. fixed mindset) and stress (stress-is-enhancing vs. stress-is-debilitating mindset) to job performance. We hypothesized that employees with a stress-as-enhancing and a growth-oriented mindset (T1) would experience more positive affect (T2), increasing their job performance (T3). We tested these hypotheses using three-wave survey data from a sample of employees in various occupations. Our results showed that employees with a growth mindset and those who viewed stress as an experience that enhances learning, vitality, and productivity experienced more positive emotions one month later. The data also showed that performance was significantly predicted by growth mindset both directly and indirectly, while stress mindset was linked only to positive affect. © 2025 Taylor & Francis Group, LLC.